A systematic approach to public health – Novel application of the human factors analysis and classification system to public health and COVID-19. (August 2021) - Bickley, Steve J.; Torgler, Benno
Highlights: We connect HFACS to the public health literature and introduce HFACS-PH. We overlay causal error and latent failure chains from the cited literature. Leveraging HFACS-PH proactively, we can more effectively address systemic issues. Interventions can be targeted across tertiary, secondary, and primary health. We also present the HFACS-PH nanocode schema in Supplementary Material. Abstract: In this article, we argue for a novel adaptation of the Human Factors Analysis and Classification System (HFACS) to proactive incidence prevention in the public health and in particular, during and in response to COVID-19. HFACS is a framework of causal categories of human errors typically applied for systematic retrospective incident analysis in high-risk domains. By leveraging this approach proactively, appropriate, and targeted measures can be quickly identified and established to mitigate potential errors at different levels within the public health system (from tertiary and secondary healthcare workers to primary public health officials, regulators, and policymakers).